Pencegahan Kelelahan Kerja Pada Sektor Informal Pekerja Penggilingan Padi: Literature Review - Damairia Hayu Parmasari (Indonesian Journal of Health Community, 2024)
The informal sector is one of the sectors that has not yet implemented many aspects of Occupational Safety and Health (K3). This is due to the lack of awareness of workers and supervision from various parties for the implementation of K3. K3 needs to be implemented in the informal sector including rice mills because this environment has the potential for danger and risk that can cause accidents and work fatigue. Work fatigue needs to be prevented to prevent work accidents. The purpose of the study was to determine the prevention of work fatigue in the informal rice milling sector. The research method was a literature review. Literature review was carried out using the Google Scholar search engine. The results of the literature search obtained 7 articles related to work fatigue factors and prevention of work fatigue. The article recommends that work fatigue needs to be prevented to increase work productivity in rice mill workers. The conclusion of the study is that rice mill workers need to prevent work fatigue by stretching their muscles while working, consuming enough water to prevent dehydration, and improving work postures to be more ergonomic to prevent work fatigue.